Pengaruh Audit Tenure, Audit Fee, Audit Capacity Stress serta Spesialisasi Auditor terhadap Kualitas Audit - Fitriani, Heppy; Challen, Auliffi Ermian (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The purpose of this study is to investigate the impact of auditor specialization, audit tenure, audit fee, and audit capacity stress on audit quality. The descriptive-quantitative technique is applied in this study. The population of manufacturing businesses in the consumer products sector that were listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021 is used in this study. The sampling method employed in this study is purposive sampling, produced a sample of sixteen firms. The yearly financial reports from the Indonesian Stock Exchange's official website are the secondary data used in this study (IDX). Using SPSS version 29.0, logistic regression is the analytic approach employed. The findings demonstrated that there was no relationship between audit quality and auditor specialization, audit tenure, dan audit capacity stress. Audit fees, however, have a detrimental impact.